Review of polymer technologies for improving the recycling and upcycling efficiency of plastic waste. (April 2023) - Jung, Hyuni; Shin, Giyoung; Kwak, Hojung; Hao, Lam Tan; Jegal, Jonggeon; Kim, Hyo Jeong; Jeon, Hyeonyeol; Park, Jeyoung; Oh, Dongyeop X.
Abstract: Human society has become increasingly reliant on plastic because it allows for convenient and sanitary living. However, recycling rates are currently low, which means that the majority of plastic waste ends up in landfills or the ocean. Increasing recycling and upcycling rates is a critical strategy for addressing the issues caused by plastic pollution, but there are several technical limitations to overcome. This article reviews advancements in polymer technology that aim to improve the efficiency of recycling and upcycling plastic waste. In food packaging, natural polymers with excellent gas barrier properties and self-cleaning abilities have been introduced as environmentally friendly alternatives to existing materials and to reduce food-derived contamination. Upcycling and valorization approaches have emerged to transform plastic waste into high-value-added products. Recent advancements in the development of recyclable high-performance plastics include the design of super engineering thermoplastics and engineering chemical bonds of thermosets to make them recyclable and biodegradable. Further research is needed to develop more cost-effective and scalable technologies to address the plastic pollution problem through sustainable recycling and upcycling. Graphical abstract: Image 1 Highlights: Summarized recent advances for increasing plastic recycling/upcycling efficiency. Reviewed technologies for converting plastic waste into other polymer materials. Materials with higher performance than the input plastic waste can be manufactured.